2017
DOI: 10.18632/oncotarget.14505
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer and chronic obstructive pulmonary disease: From a clinical perspective

Abstract: Chronic obstructive pulmonary disease (COPD) and lung cancer are devastating pulmonary diseases that commonly coexist and present a number of clinical challenges. COPD confers a higher risk for lung cancer development, but available chemopreventive measures remain rudimentary. Current studies have shown a marked benefit of cancer screening in the COPD population, although challenges remain, including the common underdiagnosis of COPD. COPD-associated lung cancer presents distinct clinical features. Treatment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 120 publications
(162 reference statements)
1
32
0
4
Order By: Relevance
“…Lung cancer research is currently characterized by a tremendous amount of new insights and approaches ranging from genetics [ 1 ] over novel treatment options [ 2 ] to diagnostics [ 3 5 ] and prevention [ 6 , 7 ]. In the past two decades, there has been an increased focus on gender differences in health and disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer research is currently characterized by a tremendous amount of new insights and approaches ranging from genetics [ 1 ] over novel treatment options [ 2 ] to diagnostics [ 3 5 ] and prevention [ 6 , 7 ]. In the past two decades, there has been an increased focus on gender differences in health and disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiologic studies and lung cancer screening trials have shown a two- to four-fold increase in lung cancer risk in patients with COPD in comparison with non-COPD smokers [ 12 ]. This risk is highest when airflow obstruction and emphysema coexist in a patient [ 17 ]. Squamous cell carcinoma in particular is more commonly seen in patients with COPD, and tumor localization strongly associates with areas with the highest degree of emphysema [ 17 ].…”
Section: Aging Lung Diseases May Overlapmentioning
confidence: 99%
“…This risk is highest when airflow obstruction and emphysema coexist in a patient [ 17 ]. Squamous cell carcinoma in particular is more commonly seen in patients with COPD, and tumor localization strongly associates with areas with the highest degree of emphysema [ 17 ].…”
Section: Aging Lung Diseases May Overlapmentioning
confidence: 99%
“…Lung cancer and COPD are interrelated pulmonary diseases. 10 They share many common risk factors, such as cigarette smoking and other inhalation hazards from occupational, domestic, or outdoor air pollution. 11 15 The association between COPD and lung cancer risks has been studied extensively over the last 30 years.…”
Section: Introductionmentioning
confidence: 99%